Real Implementation of Information Literacy in the Community for Library Service Transformation Program Based on Social Inclusion - Hidayah, Ahmad (INDONESIAN JOURNAL OF SUSTAINABILITY, 2025)
ABSTRACT  Libraries are desired as institutions that manage collections of written works, printed works, and/or peer works professionally with a standardized system to meet the educational, research, preservation, information and recreational needs of the users. Therefore, librarians who work in libraries must be professional in managing a library.  As  stated  in  Law  No.  43  of  2007  concerning  Libraries,  namely  "A librarian is someone who has competencies obtained through education and/or training in librarianship  and  has  the  duties and  responsibilities  to  carry  out library management and services". This means that librarians are employees who are able to manage and develop libraries with their competence. Realizing social inclusion-based library services is a necessity for equitable distribution of information and knowledge through libraries. Public information literacy supported by service innovation by librarians in libraries will make a barrel to increase interest in reading in Indonesia with the support of adequate collection availability, competent librarians and adequate Information Technology support. Key Word : Library, Librarian, Literacy, Library Services